THE ASSOCIATION BETWEEN BETEL QUID CHEWING AND METABOLIC SYNDROME AMONG URBAN ADULTS IN THE MANDALAY DISTRICT OF MYANMAR - Aung, Aye Aye; Zin, Sai Ni Soe; Ko, Aung Ko; Thet, Aung Cho (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION As the prevalence of the metabolic syndrome, obesity and diabetes increases worldwide, the need to identify modifiable lifestyle risk factors increases, especially those that may be relatively unique to a specific population. To explore a possible association between betel quid chewing and metabolic syndrome (MS). METHODOLOGY This was a community-based cross-sectional study done in Dhamma Hall, a Buddhist temple. Participants were 391 adults residing in the Chan Aye Thar Zan Township in the Mandalay District of Myanmar. We interviewed the subjects and measured their triglycerides, HDL-Cholesterol (HDL), glucose, waist circumference, body mass index and blood pressure. The main outcome measures were betel quid chewing status and the presence of MS. Other risk factors for MS (age, sedentary lifestyle, family history of DM, hypertension, and cardiovascular disease, and risk factors for non-communicable disease such as sex, smoking, alcohol use), were adjusted through multivariate regression analysis. RESULTS The prevalence of MS was similar in chewers (n=182) and non-chewers, at about 50%. After controlling for other factors, the predictors for development of metabolic syndrome among betel chewers was the daily number of quids (Adjusted OR 1.47, CI 1.10- 3.30), age 40 years and older (AOR 2.23, CI 1.28 – 3.92), family history of hypertension (AOR 0.38, CI 0.21- 0.68), and family history of diabetes (AOR 0.10, CI 0.03- 0.32). CONCLUSION Betel quid chewing may represent a behavioral lifestyle target for approaches to reduce the incidence of metabolic syndrome.